1998
DOI: 10.1523/jneurosci.18-02-00698.1998
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory Amino Acid Transporters of the Salamander Retina: Identification, Localization, and Function

Abstract: The rapid re-uptake of extracellular glutamate mediated by a family of high-affinity glutamate transporter proteins is essential to continued glutamatergic signaling and neuronal viability, but the contributions of individual transporter subtypes toward cellular physiology are poorly understood. Because the physiology of glutamate transport in the salamander retina has been well described, we have examined the expression and function of glutamate transporter subtypes in this preparation. cDNAs encoding five di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
0
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(122 citation statements)
references
References 44 publications
6
115
0
1
Order By: Relevance
“…However, subsequent experimentation established that VGlut1, 2 and 3 are present on vesicular membranes and function as glutamate transporters (Bellocchio et al, 2000;Takamori et al, 2000). By contrast with the plasma membrane glutamate transporters (Eliasof et al, 1998), vesicular glutamate transporters are sodium-independent and exhibit a more than 10-fold lower Km (2 mM: Bellocchio et al, 2000). In place of sodium-dependence, glutamate uptake into vesicles relies primarily on the electrical component (ΔΨ) of the electrochemical gradient across the vesicle membrane.…”
Section: Vesicular Glutamate Transportersmentioning
confidence: 99%
“…However, subsequent experimentation established that VGlut1, 2 and 3 are present on vesicular membranes and function as glutamate transporters (Bellocchio et al, 2000;Takamori et al, 2000). By contrast with the plasma membrane glutamate transporters (Eliasof et al, 1998), vesicular glutamate transporters are sodium-independent and exhibit a more than 10-fold lower Km (2 mM: Bellocchio et al, 2000). In place of sodium-dependence, glutamate uptake into vesicles relies primarily on the electrical component (ΔΨ) of the electrochemical gradient across the vesicle membrane.…”
Section: Vesicular Glutamate Transportersmentioning
confidence: 99%
“…Glutamate transport into glia is well characterized and is mediated by GLAST (EAAT1) and GLT-1 (EAAT2) transporters in Müller cells (Lehre et al, 1997;Eliasof et al, 1998).…”
Section: Indirect Modulationmentioning
confidence: 99%
“…For example, Arriza et al (1997) demonstrated that a large part of the glutamateevoked current mediated by EAAT5 is due to its anion conductance. Mü ller cells of some species have been reported to express EAAT5 (Eliasof et al, 1998a). However, the existence of EAAT5 in Mü ller cells from a mammalian retina remains to be demonstrated (Pow, 2001a).…”
Section: Electrogenic Glutamate Transporter Activitymentioning
confidence: 99%
“…EAAC1 (EAAT3) is present in neurons in the inner retina (Rauen et al, 1996;Schultz and Stell, 1996). EAAT4 has been reported in retinal astrocytes (Ward et al, 2004), while EAAT5 is localized to photoreceptors, bipolar cells, and possibly some Mü ller cells (Arriza et al, 1997;Eliasof et al, 1998a;Barnett and Pow, 2000).…”
Section: Introductionmentioning
confidence: 99%